The DRESDYN precession experiment - Stefani, Frank; Anders, Sten; Eckert, Sven; Freyer, Nico; Gerbeth, Gunter; Giesecke, André; Gundrum, Thomas; Kaever, Peter; Kumar, Vivaswat; Pizzi, Federico; Räbiger, Dirk; Šimkanin, Ján; et al. (Comptes Rendus. Physique)
The most ambitious project within the DREsden Sodium facility for DYNamo and thermohydraulic studies (DRESDYN) at Helmholtz-Zentrum Dresden-Rossendorf (HZDR) is the set-up of a precession-driven dynamo experiment. After discussing the scientific background and some results of water pre-experiments and numerical predictions, we focus on the numerous structural and design problems of the machine. We also outline the progress of the construction work and give an outlook for the upcoming experimental campaigns.